(untitled) (TSUL LEGAL REPORT, 2026)
The article analyzes the priorities for improving the activities of the mass media in the field of public control, including the opinions of several scientists about the activities of the mass media in the implementation of public control, as well as the legal basis of public control. In addition, in the civil society that is being established in our country, state authorities and officials are under the control of the general public based on the Constitution and laws, and state agencies and officials are “hired servants” of civil society and are responsible to the people, in particular, the principles of communication with the people, the state to citizens. It is highlighted that the principles of service provision are important in ensuring the implementation of laws on the liberalization of public life, as well as public control over the activities of state authorities and management bodies; in a word, establishing a sufficient level of public control is a requirement of today. At the same time, proposals and recommendations have been developed in order to further accelerate reforms in the way of building a civil society and to improve the activities of mass media directly related to public control in ensuring the rule of law.